Profile of occupational eye injury at an ophthalmologic emergency department - Matos, Alexis Galeno (Rev Bras Med Trab, 2017)
BACKGROUND: Eye injury is the most frequent reason for visits to ophthalmological emergency departments, being one of the leading causes of avoidable blindness worldwide and having considerable socioeconomic impact on health systems and populations. OBJECTIVE: To establish the epidemiologic profile of eye injuries caused by work accidents, visual sequelae and socioeconomic impact. METHODS: A retrospective, cross-sectional study was conducted by reviewing the medical records of patients with occupational eye injury treated at an ophthalmologic emergency department from April to August 2016. RESULTS: A total of 112 patients were included, all of them male. The most affected age group was 31 to 35 years old, and the main professional category the one of mechanics; foreign bodies on the eye surface represented 85% of injuries; 72% of patients sought specialized treatment more than 12hours after the accident; and for 86% this was their first treatment at the company. Half of the patients used personal protective equipment. In most cases the final visual acuity after injury was not impaired. CONCLUSION: Although most patients did not remain with visual sequelae, occupational eye injury resulted in loss of working days and expenses with medication. Studies such as the present one contribute to the mapping of the investigated problem and to the formulation of preventive strategies.